2021
DOI: 10.3390/nu13072220
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hyaluronan Relieves Wrinkles and Improves Dry Skin: A 12-Week Double-Blinded, Placebo-Controlled Study

Abstract: Hyaluronan (HA) is present in all connective tissues and organs, including the skin and joint fluid. However, few clinical trials have comprehensively evaluated the impacts of oral HA on skin conditions, including wrinkles and moisturization. In this study, we conducted a placebo-controlled, randomized, double-blind trial of daily HA (120 mg) intake for 12 weeks in 40 healthy Asian men and women (aged 35–64 years). Skin condition was determined by the evaluation of wrinkles, stratum corneum water content, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
1
16
1
1
Order By: Relevance
“…Hyaluronan was examined in four studies ( 65 – 68 ) ( n = 196) as a single-preparation over 4 to 12 weeks. The daily dosages of hyaluronan were 120 mg in three RCTs and 200 mg in one RCT, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyaluronan was examined in four studies ( 65 – 68 ) ( n = 196) as a single-preparation over 4 to 12 weeks. The daily dosages of hyaluronan were 120 mg in three RCTs and 200 mg in one RCT, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…No researches containing hyaluronan as a combination preparation reported the effect on moisturization. For the outcome of TWEL, both the researches of Michelotti 2021 ( 67 ) and Hsu 2021 ( 65 ) reported that the HA group displayed significantly lower transdermal water loss in the face over 4 to 12 weeks of intervention. Non-remarkable differences in the arms versus the placebo group were revealed by the RCT of Hsu 2021, which requires further validation in the future.…”
Section: Resultsmentioning
confidence: 99%
“…A study in hairless mice also revealed that collagen hydrolysate intake mitigated the loss of epidermal barrier function and skin elasticity induced by ultraviolet radiation [ 23 ], confirming the role of collagen supplements in restoring the skin barrier function. Oral HA has also been shown to relieve wrinkles and dry skin in long-term clinical studies [ 24 ]. The effect of HA on collagen synthesis has also been explored in in vitro and in vivo studies [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that skin dryness was largely decreased in dorsal skin through HA oral injection to hairless mice under UV conditions [29]. In clinical study, skin hydration and elasticity as well as stratum corneum water content was dramatically increased after hyaluronan solution oral administration [30,31]. With stronger pursuit of beauty, HA is largely used in surgical techniques to prevent facial aging, especially in lower areas of the face [32].…”
Section: Discussionmentioning
confidence: 99%